If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3y+5=y-7
We move all terms to the left:
-3y+5-(y-7)=0
We get rid of parentheses
-3y-y+7+5=0
We add all the numbers together, and all the variables
-4y+12=0
We move all terms containing y to the left, all other terms to the right
-4y=-12
y=-12/-4
y=+3
| -8x+5=-114 | | 2(5x+5x)=10+50 | | 5d-7-d+4= | | 5y-2)=-21 | | 3x-4=8x+13 | | 18.51+4.8v=2.61+3.8v | | 4b=94 | | -9x-4=-95 | | -6+(x+4)=18 | | s3.7=5 | | 100+140+110+115+135+x=720 | | 4x+9=427 | | 2+9d=65 | | D=20×g | | 5v-(3+v)=30 | | 0.50x+50=200 | | 12-17u=-18u | | 3x+2(11+2x)=-13 | | X-4=8/3x+13 | | 7(2p+5)=3(12+5p)-p | | 6h-18=7h+1 | | 12=n2.1 | | r/28=24 | | x+18+24=54 | | 8(k+1)=72 | | -20-7p=18-11p+14 | | |x−3|=|3x+4| | | 6(j-86)=60 | | 3(x+7)=4x+20 | | -1.1r=+0.3+r+5.5 | | 15^x=79 | | 10/x-3=5/6 |